Incubation or Induction? Gendered Identity Work in the Context of Technology Business Incubation. (July 2015) - Marlow, Susan; McAdam, Maura
While there is a substantial body of literature exploring the influence of business incubation upon early stage firms, this debate remains almost entirely gender blind. This article challenges this assumption by adopting a feminist perspective to reveal business incubation as a gendered process shaping the identity work undertaken by women seeking legitimacy as technology venturers. In so doing, we critically evaluate prevailing normative analyses of the business incubation process and entrepreneurial legitimation. To illustrate this argument, we draw upon empirical evidence which reveals technology incubation as a legitimating induction process encouraging women to reproduce masculinized representations of the normative technology entrepreneur.